Corneal Crosslinking With Rose Bengal and Green Light: Efficacy and Safety Evaluation. Issue 9 (September 2016) - Zhu, Hong; Alt, Clemens; Webb, Robert H.; Melki, Samir; Kochevar, Irene E.
Abstract : Purpose: To evaluate crosslinking of cornea in vivo using green light activation of Rose Bengal (RGX) and assess potential damaging effects of the green light on retina and iris. Methods: Corneas of Dutch belted rabbits were de-epithelialized, then stained with Rose Bengal and exposed to green light, or not further treated. Corneal stiffness was measured by uniaxial tensiometry. Re-epithelialization was assessed by fluorescein fluorescence. Keratocytes were counted on hematoxylin and eosin (H&E)–stained sections, and iris cell damage was assessed by lactate dehydrogenase staining. Thermal effects on the blood–retinal barrier (BRB) were assessed by fluorescein angiography and those on photoreceptors, retinal pigment epithelium (RPE), and choriocapillaris by light microscopy and transmission electron microscopy. Results: RGX (10-min irradiation; 150 J/cm 2 ) increased corneal stiffness 1.9-fold on day 1 (1.25 ± 0.21 vs. 2.38 ± 0.59 N/mm; P = 0.036) and 2.8-fold compared with controls on day 28 (1.70 ± 0.74 vs. 4.95 ± 1.86 N/mm; P = 0.003). Keratocytes decreased only in the anterior stroma on day 1 (24.0 ± 3.0 vs. 3.67 ± 4.73, P = 0.003) and recovered by day 28 (37.7 ± 8.9 vs. 34.5 ± 2.4, P = 0.51). Iris cells were not thermally damaged. No evidence of BRB breakdown was detected on days 1 or 28. Retina from RGX-treated eyes seemed normal with RPE cells showing intact nuclei shielded apically by melanosomes, morphologically intact photoreceptor outer segments, normal outer nuclear layer thickness, and choriocapillaris containing intact erythrocytes. Conclusions: The substantial corneal stiffening produced by RGX together with the lack of significant effects on keratocytes and no evidence for retina or iris damage suggest that RGX-initiated corneal crosslinking may be a safe, rapid, and effective treatment.